PENGARUH PERBEDAAN WAKTU AWAL PEMBERIAN PAKAN BUATAN TERHADAP PERTUMBUHAN DAN AKTIVITAS ENZIM PENCERNAAN LARVA IKAN KERAPU BEBEK CROMILEPTES ALTIVELIS (VALENCIENNES 1828) - Melianawati, Regina; Pratiwi, Rarastoeti; Astuti, Ni Wayan Widya (JURNAL BIOLOGI INDONESIA, 2012)
The effect of different initial time of artificial feeding to the growth and the activities of digestive enzymes of humpback grouper larvae Cromileptes altivelis (Valenciennes 1828).Humpback grouper is an economically marine finfish commodity, so it is important to scale up its culture. In aquaculture, feed is dominantly affecting to fish growth. Besides live feeds, theartificial feed is also given to fulfill the need of nutrient for larvae. However, the capability of larvae to digest the artificial feed is still limited because of its simplicity and immaturity of digestive system structure. Digestive enzymes are a biological indicator to figure out the capability of larvae to digest the artificial feed. This research was conducted to find out the influence of different initial time of artificial feeding to the growth and digestive enzyme activity of humpback grouper larvae. Larvae rearing were done in hatchery. Larvae were fed with live feed rotifers started in the evening of the second day. The treatment given in this research was the difference initial time of artificial feeding, i.e: (A) given at 8 days old larvae and (B) given at13 days old larvae. The variable observations were the growth and digestive enzyme activity of larvae. The results indicate that the different initial time of artificial feeding influenced to thegrowth and digestive enzyme activity of humpback grouper larvae. Total length, body weight, length of dorsal spine and ventral spine of 30 days old humpback grouper larvae on treatment A were 17.47±2.35 mm, 0.11±0.04 g, 6.83±0.45 mm and 5.07±0.50 mm, respectively, while on treatment B were 13.23±2.53 mm, 0.04±0.02 g, 5.73±1.11 mm and 4.48±0.50 mm, respectively. Up to 30 days old larvae, protease and amylase enzymes activities of larvae on treatment A was higher than on treatment B, while lipase enzymes activity of larvae on treatment B was higher than on treatment A. Therefore, the different initial time of artificial feeding gives the different effect on the growth and the activities of protease, amylase and lipase enzymes of humpback grouper larvae.Key words: artificial feed, growth, digestive enzyme activity, humpback grouper, larvae